STRATEGI TIM REDAKSI DALAM MENINGKATKAN KUALITAS PRODUKSI SIARAN “BORGOL” DI LEMBAGA PENYIARAN TELEVISI LOKAL (I NEWS PALEMBANG) - Fitri Hidayatul Khasanah; Aliasan Aliasan; Hartika Utami Fitri (Social Science and Contemporary Issues Journal, 2023)
ABSTRACT: This study examines the editorial team's strategy to improve the production quality of the "Handcuffs" broadcast on iNews TV, a local television broadcasting institution in Palembang. According to a Nielsen survey, the Detak Palembang program has an audience of more than 90% of Palembang people, and images are very important for television broadcasts. Images must be attractive and high quality. The producer is responsible for leading the entire production team to achieve the goals that have been set together in terms of creative and production management in accordance with the agreed themes and topics. Therefore, producers must be creative and have their own strategies so that the resulting images are good and quality broadcasts. Next, the researcher gave the title of the problem: "What is the editorial team's strategy for improving the production quality of handcuff broadcasts at the local television broadcaster iNews TV." In addition, the aim of this research is to determine innovative methods that producers can use to improve image quality in Palembang iNews events. There were two informants for this research, namely the Producer and Chief Editor of the iNews TV handcuff program. This research uses a qualitative descriptive approach with data collection techniques through observation, interviews and documentation. Researchers found that iNews TV producers used strategies to get a good angle when reporting, so they could describe the atmosphere at the scene correctly. Producers also ensure that their images are not shaky. KEYWORDS: Creative Strategy, iNews Handcuffs, Palembang, Image Quality.